Collaborative workflow modelling based on activity diagrams, coloured petri-nets and system dynamics - Pudhota, Leo (Curtin University, 2012)
This thesis addresses one of the most challenging issues in today‘s dynamic, complex and fast changing business environment: Collaborative Workflow Management. It provides methods on how to model complex, large-scale collaborative business processes, inter-dependent relationships between the organisations, and heterogeneous collaboration entities, to help re-engineer IT-based Workflow Management Systems, and to enable inter-operability and information sharing to overcome traditional closed-wall-based legacy systems which cannot easily work together and cause lower productivity.This thesis defines different types of collaborative workflows, namely: intra-organisation collaborative workflow, inter-organisation collaborative workflow, and heterogeneous organisation collaborative workflow, and the challenges each of these are facing. The contribution of this thesis is that it developed several techniques to support collaborative workflow modelling, design, implementation and management of large-scale, complex collaborative environments including Extended Activities Diagrams, Coloured Petri-nets, System Dynamics Modelling, Managerial Administrative Operational (MAO) Workflow Model, Service Oriented and Self-organisation Workflow Management.In order to provide proof of concept, the thesis chose the transport logistics industry as a test-bed. The practical issues were drawn from two industry collaborators, namely: Seapower Resource International on the Central Coast, NSW, and a virtual collaborative logistics consortium partnership and Fremantle Port Vehicle Congestion Management. The long overdue core issue has been the provision of seamless information communication and real-time information sharing between big or small-medium logistics enterprises for productivity management, and the underlying challenge has been the provision of a virtual infrastructure that virtually integrate the partners with effective IT-based workflow management, so that it can effectively facilitate the coordination, and cooperation as well as real-time tracking and tracing of goods and services across the supply chain in the regions and beyond borders in collaborative partnership businesses. This thesis also laid out the challenges of existing work and possible future solutions.